The Structure of the Cannibal Sludge flocs generated under the fast and the slow feed conditions and their Digestibility - Passkorn Khanthongthip; John T. Novak (Case Studies in Chemical and Environmental Engineering, 2023)
An activated sludge system that incorporates a sidestream anaerobic bioreactor, called the Cannibal process, generated about 60 % less solids than conventional activated sludge without any negative effects on the effluent quality. In addition, operating the Cannibal process with different feeding patterns can result in different system performance. When the feed is provided to the Cannibal system over a period of 5 minutes (fast feed), the system generates less solid than the Cannibal system fed over a period of 4 hours (slow feed). In this study, the cation exchange resin (CER) and sulfide addition procedures were utilized to extract the Cannibal sludge flocs generated under the fast and the slow feed conditions to gain a fundamental insight on the structure and their components of those flocs. In addition, the fast and the slow feed Cannibal sludge was anaerobically and aerobically digested to evaluate the effect of feeding patterns on their digestibility. It was found that the readily biodegradable (1 kDa.) CER and sulfide extracted protein is larger in the flocs from the fast feed than the slow feed Cannibal system. When these two different types of flocs were anaerobically digested, the major fractions to be degraded were the sulfide extractable proteins. It was also found that the proteins in the fast feed Cannibal sludge flocs were degraded more than that in the slow feed Cannibal sludge flocs under anaerobic conditions. Consequently, it can be proposed that the influence of the high substrate pressure (fast feed) is to generate larger readily biodegradable proteins in the fast feed than the slow feed Cannibal sludge flocs. Because the 1 kDa. sulfide extracted proteins released from the fast feed Cannibal sludge floc are more biodegradable than that from the slow feed Cannibal sludge under anaerobic environment, it can be thought that the 1 kDa. proteins generated under the fast feed condition may consist of either many simple amino acids that are easily degradable or amino acids that microorganisms cannot produce but need to consume for their survival.
Keywords: Wastewater Treatment and Nitrogen Removal; Anaerobic Digestion and Biogas Production; Constructed Wetlands for Wastewater Treatment